Weighted membership based on matrix relation. (13th October 2017) - Elshenawy, Assem; Kamel EL‐Sayed, M.; Elsodany, E.
Abstract : Deciding participation level of a component to dubious information is essential, particularly all things considered are displaying issues. This paper will present a participation capacity of components that has a place with unverifiable information. The fundamental instrument is the similarity classes that came about because of the likeness connection of a data framework. We will likewise express a few properties and an examination between our work and the past one.